Islam Radikal-Fundamentalis vs Pancasila, Kristalisasi Kebhinnekaan: Tinjauan Kritis-Filosofis terhadap Gerakan Islam Radikal-Fundamentalis di Indonesia - Ranja, Adrianus (Perspektif, 2017)
A struggle to live out Pancasila appropriately has always to face other ideologies which in a way wants to substitute it. As the ideology of the people of the Republic of Indonesia, Pancasila has always been shakened by diverse movements for the sake of certain, particular groups.One of such groups is the socalled radical-fundamentalist Islamic movement. It has struggled to erect the syariah law in place of Pancasila. The writer tries to analyse philosophically this movement, while his position is on the other side, namely to put diversity forward as the constitutional basis of the Nation-State of the Republic of Indonesia.